IMAGES, RELICS AND DEVOTIONS AT THE COLEGIO MÁXIMO DE SAN MIGUEL`S CHURCH: ICONOGRAPHY, RELATIONS AND FUNCTIONS (SANTIAGO DE CHILE, SIGLO XVIII) - Schenke Reyes, Josefina (Revista de Historia Social y de las Mentalidades, 2015)
This paper deals with the worship objects and cultual practices that or ganize the inner space of the Colegio Máximo de San Miguel’s church (Santiago de Chile) in the course of the x VIII century, focusing on those sacred objects which are opened to the faithful and reserved not only to the clergymen. This analysis brings out the cultual specificity of each of the chappels, highlighting their devotional coherence as well as the equilibrium they manage to preserve between different types of images and cults. In this way, an strategy aimed at reinforcing the link which connects the Company and its saints to the universal Church is uncovered, one of whose main features includes the use of relics as elements underscoring the above mentioned link.